2018
DOI: 10.1016/j.physbeh.2017.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Short photoperiod reverses obesity in Siberian hamsters via sympathetically induced lipolysis and Browning in adipose tissue

Abstract: Changes in photoperiod length are transduced into neuroendocrine signals by melatonin (MEL) secreted by the pineal gland triggering seasonally adaptive responses in many animal species. Siberian hamsters, transferred from a long-day 'summer-like' photoperiod (LD) to a short-day 'winter-like' photoperiod (SD), exhibit a naturally-occurring reversal in obesity. Photoperiod-induced changes in adiposity are mediated by the duration of MEL secretion and can be mimicked by exogenously administered MEL into animals h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 64 publications
2
23
0
2
Order By: Relevance
“…These changes were dependent on the photoperiod, because only the animals that ate orange in the short day had their parameters altered, but it was also dependent on the season in which the fruit was harvested, because no differences were obtained with the orange from the northern hemisphere. Numerous studies in small rodents have shown that a long photoperiod increases fat accumulation or body weight, while the opposite was observed for a short photoperiod [30][31][32][33][34]. Our data show a similar effect on OSSD animals, which are in a short photoperiod but consuming fruit harvested in the spring.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…These changes were dependent on the photoperiod, because only the animals that ate orange in the short day had their parameters altered, but it was also dependent on the season in which the fruit was harvested, because no differences were obtained with the orange from the northern hemisphere. Numerous studies in small rodents have shown that a long photoperiod increases fat accumulation or body weight, while the opposite was observed for a short photoperiod [30][31][32][33][34]. Our data show a similar effect on OSSD animals, which are in a short photoperiod but consuming fruit harvested in the spring.…”
Section: Discussionsupporting
confidence: 65%
“…The reason why rodents increase their body mass in an LD photoperiod is not fully understood. Some authors report an increase in calorie intake or a change in diet preferences with longer photoperiods [31,32], while other studies attribute the changes to a decrease in BAT activity [35] or to activation of WAT lipolysis and browning during the SD [33]. In our study, the possibility of an increase in the fat content of the OSSD group due to diet was discarded, because no significant changes were observed in food intake or plasmatic parameters.…”
Section: Discussionmentioning
confidence: 78%
“…Some studies have shown that long term melatonin administration to rats or mice makes the white adipose tissue differentiate to brite (brown-in-white)/beige adipocytes which characteristically express UCP1 in their mitochondria (124)(125)(126). The classic brown and brite adipocytes have different origin (127).…”
Section: 2effects Of Melatonin On Ucps Of Mitochondriamentioning
confidence: 99%
“…Крім того, варто враховувати тривалість фотоперіоду, адже середньодобова концентрація мелатоніну відрізняється залежно від тривалості дня і ночі. Вплив фотоперіоду на процеси ожиріння був, наприклад, показаний для сибірських хом'ячків [13]. Для того, щоб визначити характер впливу мелатоніну на тонку кишку при ожирінні та оцінити ефективність його впливу при різних термінах введення цього гормона за умов весняно-осіннього фотоперіоду і була проведена ця робота.…”
unclassified